SISTEM INFORMASI PEMESANAN TIKET KAPAL MENTAWAI FAST KOTA PADANG BERBASIS WEB - Saeppu, Julianus; Mary, Thomson; Mulyono, Heri (Jurnal EDik Informatika, 2019)
ABSTRACT         Mentawai Fast is a company engaged in the field of transportation services. The problem is that there is no web-based ship ticket booking information system, ticket purchases are still manual or a passenger must go to the agent to buy tickets and requires a long time. In this system, it starts with analyzing the current system, which is done by output design, input design, file design. The research method used is SDLC (System Devolopment Life Cyle) with stages a). Planning, b) Analysis, c) Designing Systems and Software, d). Implementation, using design tools, namely UML (Unified Modeling Language). With the design of this ordering information system, it is expected to provide maximum service to customers and minimize errors in data processing. The benefits of this ordering information system are expected to improve service to customers and facilitate the transaction process faster and easier. Keywords: Information Systems, Tickets, Web, PHP, SDLC, UML